Positioning a Literary Work into Major or Minor Literature: Comparative Studies of Adichie’s Purple Hibiscus and Achebe’s Things Fall Apart - Melania Priska Mendrofa (PT FORMOSA CENDEKIA GLOBAL, 2023)
In World Literature, there are two divisions in literary work; major and minor. Therefore, confusion appears in judging literary works that belong to a major and minor one. Implicitly, when a literary work is categorized as World Literature, it can clarify its position as the major one. Meanwhile, in fact, there are some considerations in categorizing a literary work into major or minor categories. This paper attempts to analyze the position of two Nigerian authors and their works; Chimamanda Adichie, the newbie author, and Chinua Achebe, a professional author. Though Adichie’s name appears in the anthology of World Literature and most of her novel’s theme is about social and political power, she is still categorized as the minor one. This categorization is later analyzed through the concept of minor literature by Deleuze and Guattari. This research applied qualitative and descriptive research methods in comparing and describing major and minor work. As the result, it is the language, political theme, and collective value that can signify the position of the two novels.